Determinação do perfil de eliminação e da neuroproteção dos fármacos triancinolona acetonida e acetato de dexametasona em olhos vitrectomizados - Gabriella Maria Fernandes Cunha (2012)
Proliferative diabetic retinopathy is one of the leading causes of irreversible blindness around the world. In this disease, the newly-formed vessels are more susceptible to break, resulting in blood extravasation in the vitreous humor and the growth of fibrous tissue, which can cause retinal detachment by traction. The pars plana vitrectomy is a surgical procedure to treat proliferative diabetic retinopathy complications. In this surgery, the vitreous humor is often replaced by SO (Silicone Oil). The most common causes of surgical failure are fibrous tissue reproliferation, recurrent vitreous hemorrhage and problems related to the SO. Steroids, such as TA (Triamcinolone acetonide) have been used by intravitreal injection to treat eye diseases because of its anti-inflammatory and anti-angiogenic effects. To maintain the TA concentration within the therapeutic range repeated injections are necessary, but they may cause various damages. As an alternative to the incovenience of intraocular injections, extended-delivery systems (implants) made of biodegradable polymers are being studied. Therefore, the present work studied the elimination profile and neuroprotection of the drugs, TA and DA (Dexamethasone acetate), administered by intravitreal injections and through implants, respectively, and from that evaluate the use of implants as a clinical alternative for the treatment of complications related to the use of SO in vitrectomy surgery. The concentration of drugs was determined by HPLC (high performance liquid chromatograph) by extracting them from the SO. The results showed that the drug TA remained inside the vitreous cavity for five weeks and the DA drug remained no longer than the fourth week of study. Both drugs administered from different formulations presented a neuroprotective effect in the retina. However, due to increased elimination of these drugs, it is concluded the necessity of using a higher concentration as well as studying other types of polymer to prepare differents implants for use in vitrectomized eyes